Brownfield and greenfield industrial parks as an enterprise relocation strategic tool - Volodymyr Anatoliiovych Panchenko; Dmytro Mykolaiovych Zakharov (Економіка, управління та адміністрування)
The article examines the role of brownfield and greenfield industrial parks in the process of enterprise relocation, particularly in the context of Ukraine’s economic transformation. A comparative analysis of the effectiveness of both types of industrial parks is conducted regarding key parameters, such as cost, speed of implementation, environmental impact, and infrastructure availability. The advantages of brownfield projects, including the use of existing infrastructure and cost reduction, as well as the challenges associated with potential pollution and the need for remediation, are outlined. The analysis of greenfield projects demonstrated their strategic attractiveness for long-term development, although they require significant capital investments and a more extended implementation period. The instruments of state support for developing industrial parks are analyzed, including financial incentive mechanisms, tax incentives, and public-private partnership programs. The main models of industrial park management and their effectiveness in modern economic conditions are identified. The article also considers models of industrial park management, particularly the developer, community-level management, and industrialist models. It is shown that each model has its advantages and disadvantages depending on the context and strategic goals of the industrial park development. The results of the study confirm that for effective relocation of enterprises, a comprehensive approach is necessary, including state support, strategic planning, a combination of the advantages of brownfield and greenfield projects, and an optimal management model. The proposed recommendations can be used to develop a state policy to stimulate the development of industrial parks in Ukraine and attract investments in industrial infrastructure.